Apakah Harga Saham dapat Dipengaruhi Return on Equity dan Return on Investment? Studi pada Perbankan yang Terdaftar di Bursa Efek Indonesia - Maulana Dzakkiansyah; Ruhadi Ruhadi; Iwan Setiawan (Indonesian Journal of Economics and Management, 2022)
Form this study has a purpose to analyze the Effect of Return on Equity and Return on Investment on Stock Prices (Study on Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange 2016-2020 Period). Return on Investment (ROI) and Return on Equity (ROE) are both included in the Profitability Ratio. The profitability ratio was chosen because it is able to show how much profit investors get from their investment activities. So it can measure how well the company's financial performance in its operations. This study aims to determine the effect of ROI and ROE on stock prices in the banking sub-sector which is listed on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. The research method used is quantitative. Data analysis using Eviews version 10. The results of this study are expected to provide benefits for investors, academics, companies, and the community and it is hoped that this research can be used as reference material for further researchers.